Sistema de control automático para balance de luz natural y artificial en el sistema de iluminación interna de la casa autosustentable del AEIRNNR. - Román Macas, Lucia Nataly (2013)
The project likes to develop an automatic light-control-system inside an existing self-sustaining house AEIRNNR already in the National University of Loja. First the location, wherefore the system is designed, will be analysed, taking into account the positions and distribution of the actual light sources. After that, the natural light is measured inside the house, represented in luces (lux = unit of illumination), to obtain its amount and distribution during the day. One time realized this task, the best solution for the development of an automatic light-control-system is searched, which applies a balance between natural and artificial light. The basic idea is to use the natural light in an optimum way, which comes through the windows, turning off or controlling the artificial light sources if necessary. The automatic light-control-system has to measure the amount of natural light and its distribution, and based upon the values control the dimmer of the light sources and detects the variation of the natural light during the day and establishes a balance between artificial and natural light. The automatic light-control-system will be implemented using the software MATLAB. The program has to comply with the standard European UNE-EN 12464-1: 2012 on lighting indoor workplaces for workplaces inside buildings. The developed software permits to control of the artificial light sources, providing the corresponding luces, and to use the natural light in an optimum way inside the self-sustaining house.